Effects of fishery and environmental factors on a novel multispecies pot targeting European lobster (Homarus gammarus), Atlantic cod (Gadus morhua) and edible crab (Cancer pagurus) - Sara Königson; Rahmat Naddafi; Sven-Gunnar Lunneryd; Andreas C. Bryhn; Kelly Macleod; Peter Ljungberg (Frontiers in Marine Science, 2022)
Small-scale fisheries along the Swedish west coast are often operated by using small vessels, targeting multiple species by means of pots and gillnets. Fisheries using pots targeting shellfish such as European lobster (Homarus gammarus), and edible crab (Cancer pagurus) along the Swedish west coast have a relatively high economic value. However, gillnet fisheries targeting demersal fish are currently diminishing primarily due to depleted fish stocks and increased seal depredation. Small-scale fisheries are considered sustainable fisheries due to the use of selective gears and low energy consumption. To be able to retain and promote a sustainable small-scale fishery, there is a need to develop an economically viable fishery, where selective, seal-safe and sustainable gear is utilized. One potential way forward could be to develop a pot to be used for multiple target species traditionally caught in pots and gillnets. Since both shellfish and cod (Gadus morhua) can be caught in pots, the objective of this work was to develop a multispecies pot targeting lobster, edible crab and cod. Seven multi-species pots were developed and tested off the west coast of Sweden between 2015 and 2017. The catch rate, defined as catch per pot per day (CPUE) of lobster, edible crab and cod, was evaluated taking into regard fisheries-related variables such as pot type, bait, soak time, seal damage and abundance of species in the pot. The relative CPUE of lobster and cod was highest in larger pots with two chambers and three open entrances. The highest CPUE for lobster was 0.24 individuals per pot and the highest CPUE for cod was 0.17 individuals per pot. Pots with entrances equipped with funnels, preventing cod from escaping, also had a high cod CPUE (0.23 individuals per). The CPUE of crabs was not affected by pot type. For cod, lobster and crab, the CPUE significantly decreased with increasing soak time. Seal damage only occurred when cod were trapped in the pots and the CPUE of cod was higher in pots subjected to seal damage, indicating that seals raid pots specifically when cods are trapped inside.